Differential expression of genes contributing to PCD triggered by exogenous oxalic acid in tomato (Solanum lycopersicum). (27th May 2021) - Edris, Sherif; Abo-Aba, Salah; Algandaby, Mardi M.; Makki, Rania M.; Qari, Sameer H; Al-Quwaie, Diana A. H.; Jansen, Robert K.; Bahieldin, Ahmed
Abstract: The present study aims at detecting Programmed Cell Death (PCD) related genes that were triggered by exogenous oxalic acid (OA) in tomato ( Solanum lycopersicum L.). Reverse transcription polymerase chain reaction (RT-PCR) for the relative abundance of transcripts of four PCD-related genes in wild type (WT) plants resulted in increased expression levels during the time course of the treatment. The results of virus induced gene silencing (VIGS) lines corresponding to the two genes MEK2 and SGT1 retarded cell death under OA treatment for 24 h, while VIGS corresponding to the other two genes, e.g. BAK1 and plastocyanin resulted in an increased level of cell death. These results indicate that genes MEK2 and SGT1 showed apoptotic activity, while genes BAK1 and plastocyanin showed anti-apoptotic activity. It is speculated that knocking down MEK2 and SGT1 genes or over-expressing BAK1 and plastocyanin might be a possible way to retard the PCD machinery in tomato, thus can result in prolonged fruit setting time.